Rancang Bangun Alat Uji Drop Weight Impact Skala Laboratorium - Kokok Tri Budianto; Anggun Rizka Maudina; Askar Triwiyanto (Journal of Mechanical Engineering and Mechatronics, 2017)
The impact test is a test to measure the material's durabilityagainst shock loads. The impact test simulates the operating conditions of that materialoften found where the load does not always occur slowly but rathercame suddenly. The impact test instrument to be designed in this studyis a Drop Weight Tester (DWT) tool. This impact test apparatus utilizes massobjects and gravitational forces. Design of Drop Weight Tester (DWT) tool, designthe design refers to the ASTM D-5420-04 standard. In this study the designthe impact test apparatus analyzed the strength of the connection as well as the construction deflection forensure design results can be made. On testing Drop Weight Tester, objectsthe test is given a shock load with certain criteria such as altitude, load, dimensionpunch component striker as well as specimen thickness. At the same time it is doneobservation and data collection of the energy absorbed during the test.Specimen used is SPCC and Zincalume material with thicknessdifferent.